1969
DOI: 10.1017/s0003356100027008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of Barki sheep raised under semi-arid conditions

Abstract: SUMMARYRecords on 695 lambs were collected over a period of 5 years from 1961/62 to 1965/66, at Ras El-Hekma Desert Research Station, 230 km west of Alexandria. The characters studied were birth, weaning and yearling body weights, pre- and post-weaning daily gains and greasy fleece weight.Birth, 120-day and 365-day body weights were 3·4, 18·2 and 33·4 kg respectively. Greasy fleece weight at 16 months of age was 3·29 kg. Heritability estimates of birth, weaning, yearling weights, pre- and post-weaning daily ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

1972
1972
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
1
5
2
Order By: Relevance
“…The correlation coefficient between birth weight and pre-weaning average daily gain was 0-28 and highly significant <P<0-01). Shelton (1964) and Fahmy et al (1969) reported coefficients of 0-52 and -0-04, respectively, both of which differ considerably from that in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…The correlation coefficient between birth weight and pre-weaning average daily gain was 0-28 and highly significant <P<0-01). Shelton (1964) and Fahmy et al (1969) reported coefficients of 0-52 and -0-04, respectively, both of which differ considerably from that in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…The correlation between 3-and 6-month weights was much higher and its magnitude suggests that in selection of animals for 6-month weight, some pre- liminary culling may be based on 3-month weight. The correlation estimates reported here are higher than those obtained by Fahmy et al (1969) for Barki sheep in Egypt but similar to the values obtained by Farid & Makarechian (1978) in Iranian fat-tailed sheep. Six-month weight of lambs is regarded as a good indicator of their genetic potential for future growth (Bradford & Spurlook, 1972) and i» therefore an important selection criterion in meat breeds of sheep.…”
Section: Relationships Between Lamb Weights At Different Agessupporting
confidence: 79%
“…The present estimates are lower than most of those reported in the literature which range from 0-34 to 0-78 (Morley, 1955;Young, Turner & Dolling, 1960&;Hall, Ruttle & Sidwell, 1964;Brown & Turner, 1968;Mullaney et al 1970;and others). For the local breeds, Fahmy et al (1969) and Kadry (1971) working on Barki and Karam (1959) working on Rahmani, reported higher estimates than the present ones (ranging from 0-29 to 0-55).…”
Section: Genetic Parameterscontrasting
confidence: 59%
“…In agreement with these findings, Young et al (1965), Brown & Turner (1968) and Burfening, Van Horn & Blackwell (1971) reported positive genetic correlations between yearling greasy fleece weight and each of weaning and 16-month body weights. On the other hand, some other reports showed low negative genetic correlation between yearling body weight and yearling greasy fleece weight (Morley, 1955;Hall et al 1964;and Fahmy et al 1969).…”
Section: Genetic Parametersmentioning
confidence: 94%